2004
DOI: 10.1007/s00216-004-2539-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of piribedil in pharmaceutical formulations by micellar electrokinetic capillary chromatography

Abstract: A fast and simple micellar electrokinetic capillary chromatographic method was developed for the analysis of piribedil in pharmaceutical formulations. The effects of buffer concentration, buffer pH, sodium dodecyl sulphate (SDS) concentration, organic modifier, applied voltage and injection time were investigated. Optimum results were obtained with a 50 mM borate buffer at pH 8.0 containing 50 mM SDS by using a fused silica capillary (50 microm internal diameter, 72 cm effective length). The sample was injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Since the solute migration time in CE depends on its ionisation [14][15][16][17][18], we investigated the influence of the buffer pH on the migration time (Figure 1). For this purpose, four buffer compositions of different pH from 6 to 9 were selected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the solute migration time in CE depends on its ionisation [14][15][16][17][18], we investigated the influence of the buffer pH on the migration time (Figure 1). For this purpose, four buffer compositions of different pH from 6 to 9 were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium dodecylsulphate (SDS) is a basic surfactant in many MEKC experiments [14][15][16][17]. This was the main reason for choosing this surfactant for our research.…”
Section: Resultsmentioning
confidence: 99%
“…This improved attention to Piribedil suggests its potential for increased clinical application in the future [17][18][19]. Numerous approaches have been investigated to enhance the solubility of Piribedil, including the utilization of micelles [20], the development of solid lipid micro and nanoparticles [21], and the creation of hybrid nanoparticles using lecithin and chitosan [22].…”
Section: Introductionmentioning
confidence: 99%
“…The liquid chromatography methods for estimating piribedil and its metabolite in plasma were also reported [9,10] . An analytical method for estimating piribedil in pharmaceutical formulations by micellar electrokinetic capillary chromatography was also published [11] . In addition to these analytical methods, few more research articles are reported for formulation development and dissolution enhancement [12][13][14][15] .…”
mentioning
confidence: 99%